2012
DOI: 10.1620/tjem.228.17
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Differentiation-Associated Gene 5 Regulates the Expression of a Chemokine CXCL10 in Human Mesangial Cells: Implications for Chronic Inflammatory Renal Diseases

Abstract: Mesangial cells play an important role in inflammatory reactions in kidney. Although viral infections often trigger the worsening of chronic inflammatory renal diseases, the mechanisms are largely unknown. Melanoma differentiation-associated gene 5 (MDA5) is a member of RNA helicase family with a conserved Asp-Glu-x-His (DExH) box. In the present study, we examined the effect of polyinosinic-polycytidylic acid (poly IC), an authentic double-stranded RNA (dsRNA) that mimics viral dsRNAs, on MDA5 expression usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 25 publications
5
55
1
Order By: Relevance
“…In this present study, we introduced poly(I:C) into cells to test for a role of RLR signaling. We previously showed that the application of dsRNA to cells is sensed by TLRs, whereas transfected dsRNA can activate RLR signaling [26]. Our data showed that both HBEpCs and HPAEpiCs have an intact RLR signaling pathway.…”
Section: Discussionmentioning
confidence: 53%
“…In this present study, we introduced poly(I:C) into cells to test for a role of RLR signaling. We previously showed that the application of dsRNA to cells is sensed by TLRs, whereas transfected dsRNA can activate RLR signaling [26]. Our data showed that both HBEpCs and HPAEpiCs have an intact RLR signaling pathway.…”
Section: Discussionmentioning
confidence: 53%
“…Knockdown of DEC1 enhanced the poly IC-induced expression of proteins for CXCL10, CCL5, MDA5 and RIG-I, and mRNAs for CXCL10 and CCL5. CXCL10 is a chemokine that promotes the chemotaxis of lymphocytes, and is implicated in the pathogenesis of glomerular nephritis including lupus nephritis and IgA nephropathy (13). CCL5 is a chemokine that is chemotactic for leukocytes such as T-cells and eosinophils (9).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that poly IC activates the TLR3/IFN-β/MDA5/CXCL10 and TLR3/IFN-β/ RIG-I/CCL5 axes in human mesangial cells (13,16). To examine whether DEC1 is involved in these axes, the cells were transiently transfected with siRNA against DEC1.…”
Section: Effect Of Knockdown Of Dec1 On Poly Ic-induced Expression Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that TLR3 signalling in human glomerular mesangial cells induces chemokine ligand 5 (CCL5) and C-X-C motif chemokine 10 (CXCL10) via the TLR3-interferon-β (IFN-β)-retinoic acid-inducible gene-I (RIG-I)-CCL5 [21] and TLR3-IFN-β-​melanoma differentiation-associated protein 5 (MDA5)-CXCL10 axes [22], respectively.…”
Section: Discussionmentioning
confidence: 99%